Ethics and organizational leadership developing a normative model - Fryer, Mick. (Oxford ; New York : Oxford University Press, 2011)
By connecting theories of leadership and business ethics with moral philosophy and empirical research, this book sets out to develop an understanding of what comprises ethical leadership and to envisage a practicable model for contemporary organizations.
Oxford scholarship online Business and Management
Includes bibliographical references (p. [205]-213) and index.
Anwar
Keywords: Leadership -- Moral and ethical aspects; Business ethics; Normativity (Ethics)